Six New Species of Agaricus (Agaricaceae, Agaricales) from Northeast China - Shi-En Wang; Tolgor Bau (Journal of Fungi, 2024)
Agaricus belongs to Agaricaceae and is one of the most well-known macrofungi, with many edible species. More than 300 Agaricus specimens were collected during a three-year macrofungal resource field investigation in Northeast China. Based on morphological observations and multi-gene (ITS + nrLSU + tef1-a) phylogenetic analyses, six new Agaricus species, i.e., Agaricus aurantipileatus, A. daqinggouensis, A. floccularis, A. griseopileatus, A. sinoagrocyboides, and A. velutinosus, were discovered. These new species belong to four sections within different subgenera: A. (subg. Agaricus) sect. Agaricus, A. (subg. Flavoagaricus) sect. Arvenses, A. (subg. Minores) sect. Minores, and A. (subg. Pseudochitonia) sect. Xanthodermatei. Morphological descriptions, line illustrations, and basidiomata photographs of these new species are provided, and their differences from similar species are discussed.